2008
DOI: 10.1002/ibd.20275
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating IBD from IBS: Comparison of the test performance of fecal markers, blood leukocytes, CRP, and IBD antibodies

Abstract: The PhiCal Test and IBD-SCAN are highly accurate for discriminating IBD from IBS. There is only marginal additional diagnostic accuracy when the PhiCal Test and IBD-SCAN are combined with ASCA and pANCA. ASCA and pANCA have a high specificity for IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
205
3
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(231 citation statements)
references
References 34 publications
6
205
3
9
Order By: Relevance
“…Investigating 252 CrD patients, Seibold's group in Switzerland found a negative association of PABs with inflammatory CrD and revealed a trend towards small bowel disease and small bowel surgery. In contrast to the Hungarian study, this latter report did not find a significant correlation with penetrating disease behavior [31]. A multicenter study involving 109 CrD patients from five university hospitals in France and one in Luxemburg, failed to identify an association between PABs and clinical features of the disease except of a relationship between the presence of the autoantibodies and an early disease onset [30].…”
Section: Autoimmunity In Crohn's Diseasecontrasting
confidence: 77%
“…Investigating 252 CrD patients, Seibold's group in Switzerland found a negative association of PABs with inflammatory CrD and revealed a trend towards small bowel disease and small bowel surgery. In contrast to the Hungarian study, this latter report did not find a significant correlation with penetrating disease behavior [31]. A multicenter study involving 109 CrD patients from five university hospitals in France and one in Luxemburg, failed to identify an association between PABs and clinical features of the disease except of a relationship between the presence of the autoantibodies and an early disease onset [30].…”
Section: Autoimmunity In Crohn's Diseasecontrasting
confidence: 77%
“…Nevertheless, although fecal calprotectin is not specific it is exceptionally useful in assessment of inflammatory bowel disease. This examination is worth of recommendation especially in children in whom intestinal neoplasm is extremely rare and its non-invasiveness and painlessness causes that it is a promising diagnostic tool, which can supplement the standard methods [7,15,18,27,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…A study in 56 subjects found a median concentration of 0.43 mg/g (range 0.01-14.55) 11 and a more recent study (n ¼ 42) showed a median of 2.2 mg/g (range 1.8-3.3). 24 Previous studies of tumour M2-PK have included measurement in controls (Table 4). Our results suggest that separate reference ranges are required for calprotectin and lactoferrin in children aged 2-9 y and that for calprotectin a separate reference range is also required in those 60 y.…”
Section: Discussionmentioning
confidence: 99%